Association of rs6166 polymorphism with FSH receptor transcript variants and steroid production in human granulosa cell cultures. (2013) - Zalewski, Grzegorz; Wołczyński, Sławomir; Chyczewski, Lech
Abstract : Follicle stimulating hormone receptor (FSHR) genetic variation at position 2039 A > G (rs6166, p.Asn680Ser) was repetitively shown to correspond to the measures of ovarian sensitivity and the outcomes of gonadotropin stimulation. However, to date, there has been no study revealing the mechanisms behind the associations observed. The aim of the present research was to investigate the relationship between rs6166 and mRNA expression of FSHR-dependent genes such as LHCGR, CYP19A1, and FSHR itself with particular reference to the FSHR transcript variants (deletions of exon 2, 6, and 9 and insertion of a novel exon between exons 8 and 9) in the cell culture model. Steroid production and its dependency on FSHR genotype were also assessed. A total of 22 normoovulatory patients undergoing IVF treatment were recruited. Granulosa cells were obtained by ovary puncture and cultured for 7 days to regain responsiveness to FSH in a gonadotropin-free medium. Stimulation was carried out for 24 hours in a serum-depleted environment using 0.5 UI/l rhFSH. Gene expression was assessed by real-time PCR and genotype was determined by allele-specific PCR. The distribution of p.Asn680Ser genotypes was as follows: 10 homozygotes Asn/Asn, 8 heterozygotes Asn/Ser, and 4 homozygotes Ser/Ser. Expression of total FSHR in all samples studied increased by a mean factor of 1.9 (95% CI: 0.39–11.53, p < 0.001) upon stimulation. All of the analyzed FSHR transcript variants were detectable in non-stimulated and stimulated cells. The only distinct transcript that followed up-regulation was deletion of exon 2. Homozygotes Asn/Asn tended to have higher rhFSH-induced expression of FSHR as compared to the carriers of Ser/Ser genotype. Relative expression of LHCGR and CYP19A1 although up-regulated showed no significant difference with respect to the FSHR genotype. Variable modulation of FSHR expression by its own ligand is likely to explain different clinical behavior of patients with FSHR genetic variants. The putative contribution of rs6166 requires further investigation.